Structural characterization of volcanic ash of the nevado del ruiz: zeolite phase identification (2014)
This paper presents a study of the structural properties obtained from volcanic ash from Nevado del Ruiz located in the Central Range of Andes - Colombia. The volcanic ash samples were subjected to hydration processes and heat treatments in situ during characterization stage material. During the hydration process, which consisted of introducing 2.4875 ± 0.0002g of volcanic ash in 20ml of water for 48 hours, the organic fraction present was removed from the particulate suspension in the aqueous medium. From measurements of X-ray diffraction (XRD), it was observed, that the temperature variations between 323 and 673 K influence the phase formation of zeolite with structures Heulandite -Ca, Stellerita and gmelinite. XRD measurements were performed in vacuum and atmospheric pressure. X'pert Highscore Plus program and simulation Rietveld refinement were used for to obtain the structures of each of the phases. It was found, using the Scherrer equation, that crystallite sizes (Δ (2θ)) are influenced by changes crystal-chemical caused by hydration, heat treatment and pressure conditions during the characterization. A variation of Δ ( 2θ ) between 37 and 106.9 nm from XRD measurements was found. It was determined that from 423K in the sample of un-hydrated volcanic ash, the formation of zeolite Stellerita presents with a stable phase up to 673 K.